Socioeconomic status and anterior epistaxis in adult population - Pourya Masoudian (KeAi Communications Co., Ltd., 2018)
Objective: Little was known about the role of socioeconomic status as a risk factor for epistaxis in adult population. The objective of this study was to determine whether socioeconomic status influences the presentation to emergency department for anterior epistaxis in an adult population. Methods: Retrospective review of emergency department visits from January 2012 to May 2014. The setting is in an emergency department of a Canadian tertiary care centre. Adult patients with primary diagnosis of anterior epistaxis in the emergency department were included in this study. The main outcome was emergency department visits for anterior epistaxis visits. Results: A total of 351 cases of anterior epistaxis were included. The mean age was 70 years and 51% of patients were male. The patients were stratified into two groups based on whether their age was equal to and above, or below 75 years. Our analysis indicated that those 75 years or older in higher income quintiles have an increased risk of anterior epistaxis compared to the subjects in the lower income quintiles (P < 0.05). This association did not hold true for those younger than 75 years or for all age groups combined. Conclusion: There is an association between higher socioeconomic status and the presentation to the emergency department with anterior epistaxis in the population older than 75 years but not in younger patients. Keywords: Epistaxis, Anterior, Socioeconomicstatus, Income, Social determinants of health